2018
DOI: 10.14814/phy2.13641
|View full text |Cite
|
Sign up to set email alerts
|

Most bicarbonate secretion by Calu-3 cells is mediated by CFTR and independent of pendrin

Abstract: Bicarbonate plays an important role in airway host defense, however, its transport mechanisms remain uncertain. Here we examined the relative contributions of the anion channel CFTR (cystic fibrosis transmembrane conductance regulator, ABCC7) and the anion exchanger pendrin (SLC26A4) to HCO 3 − secretion by the human airway cell line Calu‐3. Pendrin and CFTR were both detected in parental Calu‐3 cells, although mRNA and protein expression appeared higher for CFTR than for pendrin. Targeting pendrin transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
21
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 47 publications
9
21
2
Order By: Relevance
“…These data suggest that VIP receptor activation or direct cAMP elevation with forskolin can activate both Cland HCO3secretion directly through CFTR. We found no evidence for Cl -/HCO3exchanger-mediated HCO3efflux in primary serous cells (Supplemental Figure 2), suggesting CFTR is the main HCO3efflux pathway during cAMP stimulation, agreeing with recent Calu-3 studies suggesting CFTR sustains HCO3secretion (88,89) instead of the pendrin Cl -/HCO3exchanger (90,91).…”
Section: Vip Stimulates Both Cland Hco3secretion From Airway Gland Sesupporting
confidence: 89%
“…These data suggest that VIP receptor activation or direct cAMP elevation with forskolin can activate both Cland HCO3secretion directly through CFTR. We found no evidence for Cl -/HCO3exchanger-mediated HCO3efflux in primary serous cells (Supplemental Figure 2), suggesting CFTR is the main HCO3efflux pathway during cAMP stimulation, agreeing with recent Calu-3 studies suggesting CFTR sustains HCO3secretion (88,89) instead of the pendrin Cl -/HCO3exchanger (90,91).…”
Section: Vip Stimulates Both Cland Hco3secretion From Airway Gland Sesupporting
confidence: 89%
“…Studies in the widely studied human airway cell line Calu-3 examined mechanisms of cAMP-stimulated HCO 3 - secretion. 36 These cells express a large amount of CFTR and much less SLC26A4 (pendrin). Forskolin-stimulated HCO 3 - secretion in Calu-3 cells was entirely CFTR-dependent and not affected by SLC26A4 knockdown, identifying an additional model of cAMP-stimulated HCO 3 - secretion in cells that contain both CFTR and members of the SLC26 family.…”
Section: Discussionmentioning
confidence: 99%
“…In HEK293/DRA cells and oocytes, there was no cAMP effect unless CFTR was also expressed, which led to modest stimulation. 9,10 In Caco-2 cells, cAMP inhibited DRA activity using 36 Cl to measure unidirectional fluxes, which was accompanied by less brush border DRA. 11 In murine duodenal brush border vesicle studies, cAMP increased Cl - /HCO 3 - exchange.…”
Section: Introductionmentioning
confidence: 99%
“…This secreted HCO 3 − appears to be generated by carbonic anhydrase located near the apical membrane (Shan et al, 2012). The same laboratory then reported that HCO 3 − secretion in Calu-3 cells is independent of pendrin (Huang et al, 2018), while other authors reported that CFTR acts together with pendrin channel (SLC26A4) to secrete HCO 3 − , in the same Calu-3 cells (Garnett et al, 2011). Thus, this issue is also a controversial matter.…”
mentioning
confidence: 99%